2011
DOI: 10.3390/atmos2030256
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Isotope Fractionation and Origin of Ammonia Nitrogen Volatilized from Cattle Manure in Simulated Storage

Abstract: A series of laboratory experiments were conducted to establish the relationship between nitrogen (N) isotope composition of cattle manure and ammonia emissions, potential contribution of nitrogenous gases other than ammonia to manure N volatilization losses, and to determine the relative contribution of urinary-vs. fecal-N to ammonia emissions during the initial stage of manure storage. Data confirmed that ammonia volatilization losses from manure are most intensive during the first 2 to 3 days of storage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 19 publications
11
43
0
Order By: Relevance
“…Similarly, Lee et al (2011) in a laboratory study had slightly lower NH 3 volatilization which ranged from 1 to 13%. In our study, 20% NH 4 -N volatilization loss is similar to the losses reported for urea (Clay et al, 1990) and simulated urine (Sherlock and Goh, 1985) and lower than the losses reported for surface-applied manure (Stevens and Laughlin, 1997;Lee et al, 2011;.…”
Section: Ammonia-nitrogen Volatilization From Cow Fecal Materialsmentioning
confidence: 86%
“…Similarly, Lee et al (2011) in a laboratory study had slightly lower NH 3 volatilization which ranged from 1 to 13%. In our study, 20% NH 4 -N volatilization loss is similar to the losses reported for urea (Clay et al, 1990) and simulated urine (Sherlock and Goh, 1985) and lower than the losses reported for surface-applied manure (Stevens and Laughlin, 1997;Lee et al, 2011;.…”
Section: Ammonia-nitrogen Volatilization From Cow Fecal Materialsmentioning
confidence: 86%
“…In the long-term, recognizing the source of aerial N losses from beef cattle manure and the time when N emission are highest will help with beef cattle manure management decisions. Our research complements research conducted by Thomsen [9] and Lee et al [10] and specifically considers NH3 emission from beef cattle manure with respect to time after fresh manure addition. Compared to 15 N-labeled urine obtained from the animal, the applicability of synthetic 15 N-labeled urine would allow advanced control over the 15 N concentration in the manure mixture and provides a less costly and time-consuming alternative.…”
Section: Introductionmentioning
confidence: 83%
“…Isotope ratio mass spectrometry is typically used to determine the ratio of 15 N and 14 N of plant and soil samples with high accuracy to detect even small differences between isotopic abundances of sample and standard conditions [7,8]. Few studies have been conducted that discuss labeled N movements through manure management systems [9,10] and have focused on compost [11][12][13] and anaerobic systems [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed increase in NH 4 + deposition at the ELA may be a result of Heavily farmed land leads to increased emissions of NH 3 to the atmosphere through the application of NH 4 + fertilizer and N as manure (Asman et al 1998). Both crop and animal farming result in NH 3 volatilization (Lee et al 2011). In Manitoba, fertilizer application increased four-fold from 1970 to 2011 (Fig.…”
Section: Historical Depositionmentioning
confidence: 99%